CLUSTER ASSESSMENT OF THE DEVELOPMENT RESULTS IN THE MARKET OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Baldzhy , M.D. (The actual problems of regional economy development, 2021)
The article considers the prerequisites for the development in the market of information and communication technologies, which is the reason for the research topic. It is substantiated that the intensive development of information and communication technologies has put humanity before the beginning of a new phase of its existence – the global information society, the transition to which, in turn, involves certain transformations in economic, social, political, legal, cultural structure of each country. The experience of developed countries in the development of the industry has been studied, which shows that the development of information and communication technologies is a catalyst for increasing the competitiveness of the national market, the country's economy, solving social and environmental problems and more. The purpose of the article is to develop a forecast development in the market of information and communication technologies for the economy of Ukraine based on the experience of developed countries. In the process of research and solution of the tasks different scientific methods were used, the main ones are: comparison, systematization, graphical analysis, clustering method, as well as the system-information approach. As a result of the analysis of the market and application of the clustering method, 9 clusters were obtained according to the similarity of the level of indicators of socio-economic and information development. This allowed to identify in detail the leaders and outsiders in the development of information and communication technologies and their impact on the national economy. The scientific novelty is the creation of clusters of countries according to the level of ICT development, which gave the right to identify the magnitude of the impact of ICT on the national economy of a country. The practical significance of the study lies in the application of existing developments to identify the situation on the world market of information and communication technologies and determine the development of Ukraine in the field of ICT.